ANATOMI SEBELAS JENIS KAYU KURANG DIKENAL DARI SUKU MIMOSACEAE, MYRISTICACEAE DAN MORACEAE - Y l Mandang (Jurnal Penelitian Hasil Hutan, 1994)
Gross and anatomical  features  of  eleven lesser known  wood species of  Mimosaceae.  Myristicaceae and  Momceae  were  observed and  described  for  identification  pueposes.   Fiber  dimension were also  measured   and  evaluated  for  their  suitability  for  pulp manufacturing purposes.Members of Mimosaceae  (Adenanthera pavonina  and Albizia chinensis) are characterized  by homoselular  ray,  paratracheal  pa-renchyma and vestured pit. Further differenttiation  is posibie  based on other characters.Members  of  Myristicaceae (Myristica maxima and  Horsfieldia sylvestris) are characterized by apotracheal banded parenchyma. vessels  mostly in radial multiples and the presence of  taniniferous tube in ray  tissue.Further differentiation  is not possible.No spesific features  Were found  for  Moraups   but  two groups  were  recognized : 1)  those brown in colour  with paratrachealparenchyma and white deposit in some of  their  vessels (5 species) :  2) those white in  colaur, aportracheal  banded,  parenchyma,withoute white deposit in vessel (2 species).  Futher  differentiation of each group is possible up to genera  level.Ten out of eleven species examined contain fibers   with medium  quality. The rest one  species, (Prainea  limpato - Moraceae) contain  fibers with poor quality.